2014
DOI: 10.1177/0959683614561885
|View full text |Cite
|
Sign up to set email alerts
|

Sediment dynamics and hydrologic events affecting small lacustrine systems on the southern-central Tibetan Plateau – the example of TT Lake

Abstract: A sedimentological, geochemical, micropaleontological, and palynological study of a lacustrine sediment record from the small TT Lake (southern-central Tibetan Plateau) shows that the background sedimentation was frequently interrupted by event-related deposits. These event-related deposits are interpreted as the result of hydrologic events that are triggered by above-average precipitation events. In total, 11 events were recorded in the TT Lake sequence. Two types can be differentiated: fluvial runoff events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 79 publications
1
11
0
1
Order By: Relevance
“…Ahlborn et al . () found a strong relationship between precipitation and sediment supply in a small catchment area on the southern‐central Tibetan Plateau. Modelling results have shown that climate variability, in particular precipitation, produce extremely fast responses throughout the catchment–fan system and overprint lower frequency tectonic variations (Allen & Densmore, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ahlborn et al . () found a strong relationship between precipitation and sediment supply in a small catchment area on the southern‐central Tibetan Plateau. Modelling results have shown that climate variability, in particular precipitation, produce extremely fast responses throughout the catchment–fan system and overprint lower frequency tectonic variations (Allen & Densmore, ).…”
Section: Discussionmentioning
confidence: 99%
“…) or unsuitable small lacustrine systems, which immediately react to local peculiarities (Ahlborn et al . ). High‐resolution records covering the Lateglacial and the Holocene are urgently needed to further assess the spatial and temporal development of moisture availability on the Tibetan Plateau.…”
Section: Palaeoenvironment Of the Southern Tibetan Plateaumentioning
confidence: 97%
“…In such a context, ostracods have already been widely used as palaeoenvironmental indicators on the Tibetan Plateau (e.g. Mischke et al ., ; Frenzel et al ., ; Wrozyna et al , , ; Mischke, ; Ahlborn et al ., ; Akita et al ., ; Alivernini et al , ). Palaeoecological applications of ostracod‐based transfer functions have proven to be a useful tool to assess palaeoclimatic conditions (Mischke, ; Viehberg and Mesquita‐Joanes, ).…”
Section: Introductionmentioning
confidence: 97%